Coverage measurement in the 2010 census - Bell, Robert M. (Robert Michael), 1951-; Cohen, Michael L. (National Academies Press, 2009)
For the 2010 census coverage measurement program, the Census Bureau is planning to focus on the goal of improving census processes. This book details the findings of the National Research Council's Panel on Coverage Evaluation and Correlation Bias.